Causes and Solution of Aperiodicity of Supersonic Flow Field Downstream of a Profile Cascade - Martin Luxa; Jaroslav Synac; Pavel Safarik; David Simurda (Communications - Scientific letters of the University of Zilina, 2012)
The paper deals with problems of transonic flow field periodicity downstream of a profile cascade with finite number of blades. The origin of phenomena generating this aperiodicity in transonic wind tunnel is described. The solution of this problem by means of adjustable perforated tailboard is documented by results of optical measurements (interferometry, schlieren methods) on a turbine profile cascade consisting of six blades only. The conditions of formation of limit load regime are described.